(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
An experiment was conducted to assess the adequacy of distinctive management practices, viz. yellow sticky trap set at 50, 100, and 150 cm height, fruit fly bait with a mashed sweet gourd (MSG), bagging, sanitation, and Ecomec 1.8 EC at the rate of 1mL per liter of water sprayed at 7 days interval. The experiment was carried out with a randomized complete block design (RCBD) with 8 treatments and 3 replications. All the treatments significantly differed from the control. The total highest number and weight of healthy fruits were recorded in bagging (41.33 and 6.08 kg) but the lowest in control (19.00 and 2.22 kg, respectively). No infested fruits were found in bagging, meanwhile, the highest number and weight of infested fruits were counted in control (13.00 and 1.27 kg). In addition, bagging appeared to have no percent of infestation by number and weight. The highest percent of fruit infestation was found in control (40.75% and 36.48%) treatments based on number and weight. No wet reduction was found in the bagging treatment and the highest percent weight reduction per fruit was recorded in Ecomec 1.8 EC (30.17%). The highest number of larval densities were found in fruit fly bait with MSG (15.83) and the lowest in a yellow sticky trap set at 150 cm height (6.7). The highest number of fruit flies in a yellow sticky trap set at 50 cm height was captured on 21 March 2021 (4.33) and the lowest was on 29 April 2021 (1.33). The highest number of fruit flies were captured in a yellow sticky trap set at 50 cm height (43/trap) and the lowest in a bait trap with MSG (9.70/bait). The highest yield and increase of yield over control were found in bagging (12.16 tons/ha and 176.10%). J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 67-82, June-December 2022